Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/cid/ciaa443
|View full text |Cite
|
Sign up to set email alerts
|

A Tool for Early Prediction of Severe Coronavirus Disease 2019 (COVID-19): A Multicenter Study Using the Risk Nomogram in Wuhan and Guangdong, China

Abstract: Background Because there is no reliable risk stratification tool for severe coronavirus disease 2019 (COVID-19) patients at admission, we aimed to construct an effective model for early identification of cases at high risk of progression to severe COVID-19. Methods In this retrospective multicenter study, 372 hospitalized patients with nonsevere COVID-19 were followed for > 15 days after admission. Patients who deterio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
410
5
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(486 citation statements)
references
References 20 publications
38
410
5
7
Order By: Relevance
“…Most of the listed complications in Fig. 1 and the related biomarkers, especially high C-reactive protein, hs-troponin, brain natriuretic peptide (BNP)/N-terminal prohormone BNT (NT-proBNP), and D-dimer, have been shown to be associated with a more severe, if not fatal, outcome of COVID-19 (1)(2)(3)(4)(5)(10)(11)(12).…”
Section: Risk Management In People Withmentioning
confidence: 99%
“…Most of the listed complications in Fig. 1 and the related biomarkers, especially high C-reactive protein, hs-troponin, brain natriuretic peptide (BNP)/N-terminal prohormone BNT (NT-proBNP), and D-dimer, have been shown to be associated with a more severe, if not fatal, outcome of COVID-19 (1)(2)(3)(4)(5)(10)(11)(12).…”
Section: Risk Management In People Withmentioning
confidence: 99%
“…Previous studies have shown several prediction models with different parameters [2,25,31,32]. Compared with other studies, the prediction effect of age, panting, and lymphopenia has been described in previous reports, while the main feature of this study is analysis of the prognostic value of IL-6 in severe COVID-19 patients for the rst time.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have indicated that in all COVID-19 patients, the incidence of severe cases is about 15% [2,3]. The mortality rate of severe COVID-19 patients is reported variously from 8% to 61.5% and signi cantly increases among the old patients [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, only one veri cation of this model has been made, the e cacy of it is doubted, and the number of patients is insu cient. Another model to early predict severe type of COVID-19 showed older age, higher LDH, CRP, RDW, DBIL, BUN, and lower ALB on admission correlated with higher odds of severe COVID-19, with the AUC reached 0.912 (95% CI 0.846-0.978) in the training set, and 0.853 (95% CI 0.790-0.916) in the validation set [5]. Nonetheless, the small sample size could be the de ciency of this model.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al, provided a nomogram to help clinicians to early identify patients who will exacerbate to severe COVID-19 but they didn't take clinical factors like underlying comorbidities in consideration which was a universally acknowledged risk factor [5]. Dong et al, used CALL score model to estimate the progressive risk of COVID-19 patients but the sample size was limited, which may cause the volatility of the result, for example the hazard ratio of LDH > 500 is 9.8 (2.8-33.8) [6].…”
Section: Introductionmentioning
confidence: 99%